Implementation of Article 56 of the Criminal Procedure Code Concerning Legal Assistance for Suspects and Defendants - Tresya Tresya; Nella Octaviany Siregar; Masriyani Masriyani (RESAM Jurnal Hukum, 2023)
The existence of the principles of equality before the law is an indication that the state is obliged to pay attention to the issue of legal aid for its citizens. Legal assistance for people or groups of people who are unable is an obligation that must be provided, because it has been regulated in Article 56 of the Criminal Procedure Code. The purpose of conducting this research is to find out the implementation of Article 56 of the Criminal Procedure Code regarding free legal assistance to suspects and defendants in the jurisdiction of Batanghari Regency. This study uses empirical juridical research using primary data sources or field data and secondary data obtained from primary, secondary and tertiary legal materials. The results of research on the implementation of Article 56 of the Criminal Procedure Code concerning free legal aid to suspects and defendants in the jurisdiction of the district are really lively and have not been implemented properly, especially at the investigation stage at the Police.